Personality as a determinant of work-family conflict - Rekha A. Priyadharshini; Reeves J. Wesley (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Extant literature reported that the perceptible experience of work-family conflict (WF conflict) is determined by any of work/family role-specific characteristics. This study is done under the premise that the perception on the occurrence of W-F conflict is influenced by person-specific personality characteristics. Authors have used big five personality dimensions as the independent variables and bi-directional nature of W-F conflict as dependent variable. It was hypothesized that extraversion, agreeableness, conscientiousness and openness positively predict W-F conflict and neuroticism negatively predicts W-F conflict. Design/methodology/approach: A self-reported questionnaire consisting of items borrowed from published literature was used to collect data. This study comprised of 205 IT/ITES (Information technology/Information technology enabled services) employees working in Chennai city. The cross sectional data was collected using snow-ball sampling technique. Findings: Structural equation modeling (SEM) was used to predict W-F Conflict by the personality dimension (The measurement model in this study is found to have good model fitness; CFI = .969; NFI = .929; RMSEA = .058; CMIN= 1.682 and TLI = .941). Results suggest that the personality dimensions such as extraversion, conscientiousness, openness to experience, and agreeableness predict W-F Conflict. Neuroticism does not appear to support our hypothesis which is contrary to predictions by extant literature. Research limitations: The sample-specific findings limit generalizability to other sectors. Cross-sectional data prohibits testing the temporal relationships among the variables. Selfreported data may result in common method biases. Hence multi-sectorial longitudinal studies may be conducted. Probabilistic sampling method may be used to eliminate common method variance. Implications: Based on the findings, it is implied that organizations could adopt personalityspecific strategies to help employees resolve W-F conflict. Originality/value: The authors believe that this is one of pioneer articles that predicted W-F conflict by personality dimensions in the global setting. This also makes significant contribution to the sector that employs the largest workforce annually.
Keywords: 650; work-family conflict; personality; big five-factor